Gestalt psychotherapy and its ontological bases - Paruzel-Czachura, Mariola (Hybris, 2013)
The article is an attempt to describe the ontological bases of Gestalt psychotherapy, both known and unknown to authors of Gestalt. Gestalt is inspired by the ancient, the modern and the contemporary philosophy. The ontological principles underlying Gestalt are holism, monism, harmony of opposites, process, cyclicality, present time and the paradoxical theory of change.